Penggunaan Koagulan Ganda dan Koagulan – Oksidator dalam Pengolahan Limbah Cair Industri Batik - Dewi Hambar Sari (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2021)
Batik wastewater contains various chemical compounds, such as dyes, synthetic compounds, heavy metals, and organic compounds that can harm the environment. Therefore, proper waste management is required. The use of alum as coagulant in textile wastewater treatment is commonly used, but it is not effective enough to remove wastewater colour and reduce COD. This study aims to modify alum-based batik wastewater treatment using (i)double coagulant by combining alum - FeSO4; and (ii)coagulant-oxidizing agent with combination of alum – chlorine. This experimental study consisted of two stages, the first experiment aimed to determine the optimum composition dose of alum – FeSO4 and alum – chlorine in depositing waste pollutants, reducing the colour and pH of the effluent; the second experiment aims to determine the effect of alum - FeSO4 and alum - chlorine at the optimum dose in reducing the COD. The results showed that alum–chlorine in various compositions reduced colour ten times and precipitated pollutants two times better than alum-FeSO4. The optimum concentration ratio of alum:chlorine is 1:1 (1.2 g/L alum : 1.2 g/L chlorine). This dose reduced the pH to 8; depositing 0.385 g pollutants; removed 99.57% wastewater colour; and decreased COD from 686.9 mg/L to 235.53 mg/L